Enhancing Business Expansion through the Integration of Artificial Intelligence and Business Intelligence - Gyandeep Yadav; Priyanka Yadav (International Journal of Electrical and Communication Engineering Technology, 2024)
Business intelligence (BI) and artificially intelligent technology (AI) give businesses a competitive edge and significantly boost growth. AI emulates human cognitive processes, learns from data, and makes intelligent decisions, while BI analyzes data for strategic insights. This study explores the synergies of integrating AI and BI, revealing opportunities for business expansion. AI algorithms analyze extensive datasets, enhancing predictions for customer behavior. The reciprocal relationship automates processes, elevates decision-making, and enables proactive strategies. The paper highlights challenges in implementation, including data quality, ethical concerns, and expertise. Capitalizing on the symbiosis between AI and BI unlocks data potential for actionable insights in today's dynamic landscape.
Keywords: Business Intelligence, Communication technology, Graphics Interface, Analytics; artificial intelligence